Tissue Distribution and Proliferation Characteristics of pVA1-like Plasmid After Infection with Vibrio parahaemolyticus in the Pacific White Shrimp Penaeus vannamei - Xingqi SU; Qiang FU; Xupeng LI; Jie KONG; Jiteng TIAN; Baoxiang CAO; Ning LIU; Sheng LUAN; Kun LUO; Xianhong MENG (Progress in Fishery Sciences)
The Pacific white shrimp (Penaeus vannamei) is currently a global mainstream aquaculture product. In recent years, as aquaculture scale has expanded, the aquaculture environment has suffered degradation, and diseases have become increasingly prevalent, severely constraining the development of the Chinese shrimp aquaculture industry. Among these diseases, acute hepatopancreatic necrosis disease (AHPND) stands out as a major cause of catastrophic economic losses. AHPND is caused by Vibrio parahaemolyticus and carried in a 69–73 kb plasmid expressing the virulence protein PirABVp. Afflicted shrimp typically exhibit symptoms such as anorexia, empty intestines and stomachs, and enlargement and softening of the hepatopancreas. Pathological studies indicate that when the toxin encounters the hepatopancreas (the target organ), it leads to the separation and disintegration of epithelial cells, turning them into substrates for bacterial replication, ultimately compromising the function of the hepatopancreas. Currently, research on AHPND primarily focuses on prevention and treatment strategies. These include adding biological agents and plant extracts to feed to enhance immunity, introducing other organisms into the water to disrupt the growth environment of V. parahaemolyticus, and analyzing the mechanism of shrimp immunity to it through bioinformatics. However, research on the distribution and amplification characteristics of pathogens within shrimp bodies is limited. Investigating the different pathways of pathogen infection in the host and the distribution and amplification characteristics of various tissues in the host after infection forms the basis of pathological research. Such research is also crucial for the scientific formulation of resistance testing methods and the accurate acquisition of resistance trait test data in breeding work. This study used selectively bred high-resistant strains of P. vannamei (average weight 35±2 g) as research subjects. Through quantitative oral infection using RT-qPCR and other techniques, P. vannamei were infected with VpAHPND in low inoculum groups (4.76×105 CFU/tail, 1.76×105 CFU/tail) (L group) and high inoculum groups (3.84×107 CFU/tail, 1.68×107 CFU/tail) (H group) at five different time points (3, 6, 9, 24, and 48 h) across nine different tissues (gill, stomach, intestine, eyestalk, muscle, hepatopancreas, fifth pleopod, abdominal nerve, and second antennae flagellum), studying the distribution and changes of PirAVp copy numbers. The amount of pVA1-like plasmid carried by V. parahaemolyticus was determined by the gene expression of the virulence protein PirAVp, which in turn represented the distribution and change characteristics of V. parahaemolyticus. The results revealed that both experimental groups experienced peak mortality between 3–6 h, with subsequent gradual decreases, and no significant difference in mortality between the two experimental groups. In the L group, plasmid copy numbers increased before decreasing in gills, eyestalk, muscle, fifth pleopod, abdominal nerve, and second antennae flagellum while they fluctuated in the stomach, intestine, and hepatopancreas. In the H group, plasmid copy numbers fluctuated in gills, intestine, eyestalk, muscle, hepatopancreas, abdominal nerve, and second antennae flagellum, with an increase before the decrease in the stomach and fifth pleopod. Among the 45 pairs of comparisons between different times within the same tissues, 32 had a significantly higher H group than the L group, 1 pair where the H group was significantly higher than the L group, one pair where the L group was significantly higher than the H group, and 1 pair where there was no significant difference. The mean plasmid copy numbers of tissues in the L group were ranked from high to low as abdominal nerve > intestine > hepatopancreas > fifth pleopod > eyestalk > muscle > gills > second antennae flagellum > stomach, and in the H group, they were ranked as abdominal nerve > intestine > gills > stomach > muscle > hepatopancreas > eyestalk > fifth pleopod > and second antennae flagellum. The average PirAVp copy numbers in the abdominal nerve and intestine tissues of both experimental groups were higher than those in other tissues, with those in the same tissues of the H group being 1.9–4.9 times higher than those in the L group. In the correlation analysis of plasmid changes between tissues of the L and H groups, there were significant correlations (P < 0.05) in plasmid changes between muscle and fifth pleopod, fifth pleopod and abdominal nerve, and gills and second antennae in the L group, while there were extremely significant correlations (P < 0.01) in plasmid changes between eyestalk and gills, and eyestalk and second antennae flagellum in the L group, and an extremely significant correlation (P < 0.01) in plasmid changes between muscle and second antennae flagellum in the H group. Conclusively, different inoculum levels not only affect the initial distribution of pathogens in the body but also lead to different changes in the body, indicating that the changes in pathogen distribution in the body are complex and unrelated among various tissues. Therefore, further research is needed on the immune mechanisms of P. vannamei against AHPND. In the overall experiment, PirAVp was detected in all tissues at all time points in both experimental groups, with the average detection levels of abdominal nerve and intestine being higher than those of other tissues, indicating that both the intestine and abdominal nerve are suitable tissues for Vibrio attachment and proliferation, warranting further exploration of the role of abdominal nerve after infection. Although the average PirAVp copy numbers in fifth pleopod and second antennae flagellum were not the highest, they were still detectable, making them potential new materials for pathogen detection in low-impact individual vitality.